EKSTRAKSI UNSUR FERRUM DARI LIMBAH PADAT PABRIK PULP DAN KERTAS - Maria Peratenta Sembiring; Desi Heltina; Chairul Chairul; Zulfansyah Zulfansyah (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2022)
Functioning industrial waste as raw material or as a product is an achievement that will continue to be optimized, especially in industries where the amount of waste is significant. Pulp and paper mills produce waste in the form of solid, sludge, liquid and gas. The objective of this research is to extract the element ferrum contained in one of the solid wastes in pulp and paper mills. By using two fatty amine extractor, lauryl amine and stearyl amine with ethanol and n-hexane as solvents. The results showed that the use of stearyl amine as an extractor and n-hexane as a solvent with operating conditions of 4 hours and a dose of 5 grams gave the best results with an extraction yield of 10,964 mg/kg.